Macroeconomic Impacts of Global Oil and Commodity Price Shocks on the Economy of Pakistan - Bilqees; Ayyub, Nadia; Shah, Mukamil (iRASD Journal of Economics, 2023)
The effects of oil and commodity price shocks on Pakistan's real exchange rate, inflation rate, government spending, money market rate, and industrial output are examined using monthly data from 2000-2017. Using the vector autoregressive (VAR) paradigm, we do an empirical investigation. Impulse response functions and generalized prediction variance decompositions are used to analyze the effect that fluctuations in oil and commodities prices have on Pakistan's economy. When the world oil price (LWOP) causes shock in the global oil market, the real exchange rate (LRER) shows a negative impulse response function. As a result of the rising cost of crude oil throughout the globe, inflation has been on the rise. Industrial output falls, the real exchange rate rises, and interest rates and inflation go up as a result of shocks. Despite increased industrial production, commodities prices have seen repercussions. Pakistan's interest rate follows shocks by rising for a prolonged period, much as the money market rate (MMR)or interest rate. After oil and commodity price shocks, governments tend to increase their spending. The real effective exchange rate is the primary source of economic volatility, as shown by generalized impulse response functions. Pakistan's economy has been hit hard by the shocks, especially the aftershocks in the currency rate. A depreciating currency rate is being seen in Pakistan. The real effective exchange rate is the main cause of fluctuations in the economy, as demonstrated by tools called generalized impulse response functions.